Learning from Practice Stories & Reflective Practice: A Narrative Analysis of Community-based Activism by Community Food System Practitioners - Kim L. Niewolny; Phil D'Adamo-Damery (Adult Education Research Conference, 2014)
Using narrative inquiry, this paper exemplifies the creation of practice stories, and the reflective practice that is embedded, that gives meaning to the place-based activism of community food system practitioners as a legitimate form of adult education. Implications for understanding and navigating ontological politics in practice are shared.